Utility of Basal Luteinizing Hormone Levels for Detecting Central Precocious Puberty in Girls - Lee, H. S.; Park, H. K.; Ko, J. H.; Kim, Y. J.; Hwang, J. S. (Hormone and Metabolic Research, 2012)
The hallmark of puberty is the progressive increase in gonadotropin-releasing hormone (GnRH) activity, reflected by an increase in the circulating concentration of luteinizing hormone (LH). The GnRH stimulation test is widely used in the evaluation of precocious puberty. The aim of our study was to assess the diagnostic utility of basal LH for the diagnosis of central precocious puberty (CPP) in girls. A total of 803 girls were referred to Ajou University Hospital for evaluation of precocious puberty between 2008 and 2011. All subjects underwent GnRH-stimulation tests as part of their evaluation. Serum LH and follicle stimulating hormone (FSH) were measured by immunoradiometric assay before and after the GnRH injection. Of the 803 subjects, 505 (62.9%) were included in the pubertal response group and 298 (37.1%) were in the prepubertal response group. Basal LH level was identified as a significant predictor for CPP. Based on the ROC curve, the optimal cut off point of basal LH related to ‘pubertal response’ was 1.1 IU/l, which was associated with 69.1% sensitivity and 50.5% specificity, with an area under the ROC curve of 0.620 (95% CI, 0.581–0.660). It is concluded that a single basal LH measurement can be used as a screening test to identify girls with CPP and to determine who should undergo GnRH stimulation test.
Keywords: luteinizing hormone; GnRH stimulation test; precocious puberty